2008
DOI: 10.1113/jphysiol.2007.149047
|View full text |Cite
|
Sign up to set email alerts
|

Simulated apnoeas induce serotonin‐dependent respiratory long‐term facilitation in rats

Abstract: Long-term facilitation (LTF) is a form of respiratory neuroplasticity frequently induced by acute intermittent isocapnic hypoxia (AIH, three 5 min isocapnic hypoxic episodes). Although repetitive apnoeas are a frequent natural occurrence producing brief (< 30 s) episodes of hypoxia and hypercapnia, it is unknown if repetitive apnoeas also elicit LTF. Apnoea-induced LTF may preserve upper airway patency during sleep, thereby limiting further apnoeic events. We tested the hypothesis that repeated, brief ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…We therefore put forward the working hypothesis that PhrX creates preconditions that enhance the subsequent induction of phrenic LTF. To be clear, we are not suggesting that PhrX is a necessary precondition for LTF but, rather, that PhrX primes the phrenic motor system, possibly by increasing phrenic motoneuron excitability, and enables more robust increases in phrenic burst amplitude following IH or other stimuli (e.g., intermittent apnea) (44,68).…”
Section: Implications For the Study Of Respiratory Ltfmentioning
confidence: 82%
“…We therefore put forward the working hypothesis that PhrX creates preconditions that enhance the subsequent induction of phrenic LTF. To be clear, we are not suggesting that PhrX is a necessary precondition for LTF but, rather, that PhrX primes the phrenic motor system, possibly by increasing phrenic motoneuron excitability, and enables more robust increases in phrenic burst amplitude following IH or other stimuli (e.g., intermittent apnea) (44,68).…”
Section: Implications For the Study Of Respiratory Ltfmentioning
confidence: 82%
“…The CO 2 apneic threshold was determined by decreasing CO 2 levels and/or increasing the ventilator rate until phrenic activity ceased, then slowly decreasing ventilator rate or increasing inspired CO 2 levels until phrenic activity resumed (the "recruitment threshold") as described previously (Mahamed and Mitchell, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Unlike modulation, plasticity implies a persistent change in a response, which continues in the absence of the stimulus. There are mixed reports in the literature suggesting that intermittent episodes of hypoxia may elicit plasticity of the AT (Ling et al, 2001; Katayama et al, 2007; Mahamed and Mitchell, 2008a; 2008b; but see Chowdhuri et al, 2010a; Xie et al, 2001), which has been speculated to result in improved breathing stability. In this study, we directly examined the effect of central neural apnea (without hypoxia) on the AT and found that only specific patterns of neural apnea result in a long-lasting decrease in the AT, an effect that is predicted to promote breathing stability by increasing the amount PaCO 2 must change to induce a subsequent apnea.…”
Section: Discussionmentioning
confidence: 99%